Achievement times of the Geography Curriculum Evaluation - Comak, Nadir; Guncegoru, Burhan (Marmara Univ, 2012)
Geography Curriculum new course in 2005 was accepted by the Board of Education 2005-2006 Education - Teaching since been implemented. The program after implementation to be held on February 17, 2009 and September 10, 2011 has been revised twice. CDOP, was accepted by Ministry of Education in 2005 publishing a revised 185-page in a book published in 2009 and 2011, however, the book was published just http://ttkb.meb.gov.tr site. CDOP published in 2005 has been prepared according to constructivist approach consists of eight main sections. Geography Curriculum consists of the success achieved in a total of 147 published in 2005 while this number decreased to 145 in 2009, revision, revision, it once again climbed up to 147 in 2011. While there was no change in the number of revisions as a result of the acquisition gains have been significant changes in content. Removing some of the gains from the program, were added some new acquisitions. Recovery according to the revisions, the numbers of learning areas have changed.
Keywords: Geography Teaching Program; achievement; curriculum; learning area; the program approach